Artesanos, cartografía e imperio. La producción social de un instrumento náutico en el mundo ibérico, 1500-1650 - Antonio Sánchez Martínez (Historia Crítica, 2019)
Explaining how and under what conditions some of the most emblematic scientific instruments of the modern world were built remains a challenge for historians of science and technology. This principle also affects nautical instruments. Thus, the objective of this article is to consider the “how” and the “under what conditions”, in a broad sense, by examining one of these devices: the nautical charts developed during the European maritime expansion. Originality: The originality of this article lies not only in the reconstruction of this instrument in Portugal and Spain, providing new information about its development process and its manufacturers, but also in shedding light on old historiographical debates that underlie the genesis of modern science, such as the difficult collaboration between practical men and theoretical men; the contribution of artisan communities to the world of knowledge; the role that practical knowledge played in the establishment of new forms of standardization in science; the adoption of an empirical methodology for achieving mastery of the world or the construction of large global empires founded upon manual labor. Methodology: Analyzing these debates requires a methodological approach that addresses the main categories and concepts put into circulation by the most recent history and philosophy of science. In short, unveiling the conditions that enabled the establishment of epistemological agreements (and also disputes) between different knowledge communities by taking a nautical instrument as “mediator.” Conclusions: The article concludes that examining empirical knowledge cultures and their material achievements are a sine qua non condition to understand the genesis of European scientific modernity and the construction of a global world.